ANALISIS TEGANGAN THERMAL PADA TROMOL REM TRUK DENGAN KAPASITAS ANGKUT 6 TON - IGN Wiratmaja Puja; Henry Ako Tampubolon; Untung Suhartanto (Mesin, 2003)
This paper presents drum brakes thermal stress analysis for 6 ton truck capacity, due to friction between shoe and drum for two leading shoe brakes type. The mechanical and thermal loading are analyzed for various road conditions such as straight path, curved, and downhill path, with various value of deceleration. Based on the transient heat transfer, the drum temperature distribution are calculated for various deceleration and braking time period. Using finite element techniques, the thermal stressses are obtained and the results are compared to the actual failures evidences of brake drums. It is obeserved that the real heat crack locations are in agreement with the computed stressed areas. Based on the pressure and temperature distribution, the wear rate can be obtained to estimate the technical life of the brake drum.